2016
DOI: 10.1111/joss.12224
|View full text |Cite
|
Sign up to set email alerts
|

School children preferences for fish formulations: The impact of child and parental food neophobia

Abstract: Child food preferences influence food choice and consumption. Thus, understanding the factors leading to the development of food likes and dislikes is important for enhancing nutritional healthy diets. This study was aimed to investigate children's acceptance of, and preferences for, three different trout formulations served at school lunch. Liking and preference were studied in relation to age, gender, and neophobic traits. Parental food neophobia, fish‐eating habits, and frequency of seafood consumption in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…However, indirectly, through negative past experiences, functional risk has a significant negative effect on frequency of consumption. This is consistent with the findings of Laureati et al [ 28 ], who find cooking methods and choosing the right recipe to be of key importance regarding young people’s acceptance of fish dishes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, indirectly, through negative past experiences, functional risk has a significant negative effect on frequency of consumption. This is consistent with the findings of Laureati et al [ 28 ], who find cooking methods and choosing the right recipe to be of key importance regarding young people’s acceptance of fish dishes.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have investigated reasons for lower-than-optimal fish consumption across the globe [ 2 ]. Several studies have explored the effect of food neophobia on fish consumption, and concluded that a higher degree of food neophobia negatively influenced fish consumption both for children [ 27 , 28 ] and adults [ 28 , 29 , 30 , 31 , 32 ]. Jaeger et al [ 32 ] showed in the case of 112 analyzed foods—among them different forms of fish—that food neophobia has a significant effect on both the frequency of the given food’s intake and on the preferences related to it.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggested that sweetness was not the only factor that influenced products’ preference. Food familiarization was reported as another component that could promote children's acceptance or preference of foods (Birch, ; Birch, Savage, & Ventura, ; Gallo, Swaney‐Stueve, & Chambers, ; Laureati, Cattaneo, Bergamaschi, Proserpio, & Pagliarini, ). For example, preschool children who were repeatedly exposed to tofu with either plain, salt, or sweet flavors, came to prefer the version that they were familiar with (Birch, ).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, food neophobia, identified as an inherent adaptive personality trait [19], was defined as the rejection of foods that are novel or unknown to the child [18]. Food neophobia may lead children to largely increase the intake of saturated fat and to reduce the consumption of vegetables, fruit, fish, and meat [20][21][22][23], thereby affecting overall food variety and dietary quality.Since children and adolescents affected by T1D fall short of meeting dietary guidelines, which include choosing a variety of foods as part of a healthy diet to maintain good metabolic control and long-term diabetes health outcomes [24,25], this maladaptive eating behavior, as well as reduced taste sensitivity, may further complicate adherence to overall diabetes management.In light of the above, the aim of the present study was to compare taste perception in children and adolescents affected by T1D with healthy controls in a cross-sectional study. As additional measurements of taste sensitivity, FP density and PROP responsiveness were also assessed.…”
mentioning
confidence: 99%
“…In this context, food neophobia, identified as an inherent adaptive personality trait [19], was defined as the rejection of foods that are novel or unknown to the child [18]. Food neophobia may lead children to largely increase the intake of saturated fat and to reduce the consumption of vegetables, fruit, fish, and meat [20][21][22][23], thereby affecting overall food variety and dietary quality.…”
mentioning
confidence: 99%